SISTEM PENGUJIAN BATERAI DENGAN METODE PULSE DISCHARGE BERBASIS XIAO ESP32 DAN DISCHARGER 150 W - Topan, Paris Ali; Fardila, Dinda (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This study developed an automated pulse discharge system using Xiao ESP32 and an optocoupler to control the battery discharge process. The optocoupler, connected to pin D7 on Xiao ESP32, is used to control the On/Off button on the constant current load device, allowing the current to be automatically applied and interrupted in a cycle consisting of active and rest periods. The system is programmed using pseudo code that utilizes the millis() function to control the duration of each discharge cycle. The test results show that the current forms a square wave pattern, where a constant current is applied during the active period and drops close to zero during the rest period, providing valuable insights into the battery’s internal resistance and Open Circuit Voltage (OCV). In conclusion, the system successfully automates the pulse discharge process with high precision, generating more accurate data for analyzing battery characteristics under dynamic load conditions, making it suitable for real-world applications such as portable devices and electric vehicles.